Legalization of Medical Marijuana Use in Legal Perspectiveand Human Rights - Andreas Sapta; Jum Anggriani; Eric Stanley (International Journal of Educational Research Excellence (IJERE), 2024)
Provisions in Law Number 35 of 2009 concerning Narcotics regulate that marijuana is included in class one. Marijuana is a narcotic which is categorized as an addictive substance with a very high scale of danger to health. Marijuana is a substance/drug that can cause a decrease or change in consciousness, loss of taste, reduce pain and is addictive (dependence). Marijuana is included in a group that cannot be used in general, but in certain doses and with the permission of the government, in this case the Minister, it can be used for the development of science. Researchers say that Marijuana makes a positive contribution, and is generally safer to consume than drugs other than Marijuana which contain many chemical ingredients, thus causing side effects in the medical world. What is discussed in this research is how the use of marijuana is regulated by law in Indonesia and whether the use of medical marijuana violates human rights in Indonesia. The research method in this writing is normative research, using a statutory approach, case approach and conceptual approach. This research concludes that regulations on the use of marijuana are contained in Law No. 35 of 2009 and the use of medical marijuana does not violate human rights.